Colonial writing and the New World, 1583-1671 : allegories of desire - Scanlan, Thomas (Cambridge University Press, 1999)
Colonial Writing and the New World, 1583-1671 offers an account of the simultaneous emergence of colonialism and nationalism during the early modern period. It suggests that colonialism is best understood as a phenomenon which had profound significance for people on both sides of the Atlantic.